Secure authentication and data aggregation scheme for routing packets in wireless sensor network - Rudramurthy Veeregowdanadoddi Chandraiah; Aparna Ramalingappa (International Journal of Electrical and Computer Engineering (IJECE), 2023)
Wireless sensor networks (WSNs) comprise a huge number of sensors that sense real-time data; in general, WSNs are designed for monitoring in various application mainly internet of things based (IoT) application. Moreover, these sensors possess a certain amount of energy i.e., they are battery based; thus, the network model must be efficient. Furthermore, data aggregation is a mechanism that minimizes the energy; however, in addition, these aggregated data and networks can be subject to different types of attacks due to the vulnerable characteristics of the network. Hence it is important to provide end-to-end security in the data aggregation mechanism in this we design and develop dual layer integrated (DLI)-security architecture for secure data aggregation; DLI-security architecture is an integration of two distinctive layers. The first layer of architecture deals with developing an authentication for reputation-based communication; the second layer of architecture focuses on securing the aggregated data through a consensus-based approach. The experiment outcome shows that DLI identifies the correct data packets and discards the unsecured data packets in energy efficient way with minimal computation overhead and higher throughput in comparison with the existing model.